Health economic analysis of ticagrelor in patients with acute coronary syndromes intended for non-invasive therapy. Issue 2 (16th September 2014) - Janzon, M; James, S; Cannon, C P; Storey, R F; Mellström, C; Nicolau, J C; Wallentin, L; Henriksson, M
Abstract : Objective: To investigate the cost effectiveness of ticagrelor versus clopidogrel in patients with acute coronary syndromes (ACS) in the Platelet Inhibition and Patient Outcomes (PLATO) study who were scheduled for non-invasive management. Methods: A previously developed cost effectiveness model was used to estimate long-term costs and outcomes for patients scheduled for non-invasive management. Healthcare costs, event rates and health-related quality of life under treatment with either ticagrelor or clopidogrel over 12 months were estimated from the PLATO study. Long-term costs and health outcomes were estimated based on data from PLATO and published literature sources. To investigate the importance of different healthcare cost structures and life expectancy for the results, the analysis was carried out from the perspectives of the Swedish, UK, German and Brazilian public healthcare systems. Results: Ticagrelor was associated with lifetime quality-adjusted life-year (QALY) gains of 0.17 in Sweden, 0.16 in the UK, 0.17 in Germany and 0.13 in Brazil compared with generic clopidogrel, with increased healthcare costs of €467, €551, €739 and €574, respectively. The cost per QALY gained with ticagrelor was €2747, €3395, €4419 and €4471 from a Swedish, UK, German and Brazilian public healthcare system perspective, respectively. Probabilistic sensitivity analyses indicated that the cost per QALY gained with ticagrelor was below conventional threshold values of cost effectiveness with a high probability. Conclusions: Treatment of patients with ACS scheduled for 12 months' non-invasive management with ticagrelor is associated with a cost per QALY gained below conventional threshold values of cost effectiveness compared with generic clopidogrel. Trial registration number: NCT000391872.